Pengaruh Kualitas Produk, Citra Merek, dan Persepsi Harga Terhadap Keputusan Pembelian - Muhammad Rifal Putra; Meylani Tuti (CV. Bimbingan Belajar Assyfa, 2026)
Background: The intensifying competition within the green and fast-moving consumer industries forces market leaders to strategically manage both brand perception and product value to secure sustainable consumer retention. Objective: This study aims to analyze the empirical effects of product quality (X1), brand image (X2), and price perception (X3) on purchasing decisions (Y) for mass commodities, specifically focusing on the Indomie brand within this contemporary framework. Method: Utilizing a quantitative approach with an associative design, data were gathered via online questionnaires from 161 active consumers selected through purposive sampling. The structural model was evaluated using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Results: The analytical results demonstrate that all three independent variables exert positive and statistically significant impacts on purchasing decisions. Based on the empirical path coefficients, contemporary brand image significantly influences the outcome (β = 0.390), alongside price perception (β= 0.355) and product quality (β = 0.270), collectively explaining 66.9% of the variance (R2 = 0.669). Conclusion: Conclusively, while all factors are critical, reframing marketing strategies to emphasize a dominant, contemporary brand image alongside strong price-benefit alignment is vital for companies to prevent customer switching and secure a sustainable competitive advantage in mass commodity markets.